Effects of coronary artery surgery on left ventricular performance, segmental wall movement, and exertional ischaemia. Issue 1 (July 1988) - Hamouratidis, N D; Handler, C E; Pipilis, A; Fiandra, A; Deverall, P B; Yates, A K
Abstract : The effects of coronary artery surgery on left ventricular performance were assessed serially by echocardiography and treadmill exercise testing in 54 patients. Patients were assessed one day before operation and again before patients left hospital (mean 10 days after operation) and one month and six months after operation. At the predischarge assessment, 41 (77%) patients showed new abnormalities of left ventricular segmental wall movement, chiefly anteroseptal hypokinesia with hyperkinesia of the posterolateral segment. Although there were no significant changes in anteroseptal wall thickening after operation, there was a significant increase in posterior wall thickening at all postoperative assessments. The frequency of this abnormality decreased progressively after operation; it persisted in 19 (35%) patients at six months. Left ventricular fractional shortening decreased after operation and at one month was significantly less than before operation. There were no significant changes in left ventricular diastolic diameter during the study. Haemodynamic function during exercise, the duration of exercise, and features of reversible myocardial ischaemia all improved progressively and significantly after coronary artery surgery. Abnormalities in left ventricular segmental wall movement and thickening commonly develop early after coronary artery surgery but tend to resolve by six months and do not seem to impair left ventricular contractility at rest or exercise performance and haemodynamic function. Recognition of these echocardiographic changes may be clinically important in the assessment of patients after cardiac surgery.